Ipteks bagi Masyarakat (IbM) Spesifikasi Proteksi Terhadap Kelompok Pemulung di Tempat Pembuangan Akhir (TPA) Kota Palembang - Kadir, A.; Dahliana, Dahliana; Sumastri, Heni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2019)
Scavengers are groups of people whose job is to collect garbage. Some of the collected waste can be processed and sold to meet their daily needs. This job as a scavenger is very at risk of infection and accidents due to work for them and their income is uncertain. This group needs special attention and assistance to improve their health and standard of living as well as to solve the problems they face. The form of assistance provided is in the form of counseling on how to prevent the occurrence of various infectious diseases and work-related accidents that can be caused by direct contact with waste that occurs continuously (every day) and also the lack of use of personal protective equipment (PPE) when scavenging.The expected results from community service activities carried out by the group of lecturers are for this group of scavengers to prevent and minimize the occurrence of infectious diseases that may arise and ensure security and safety while they work, increase income and skills to process waste materials that are useful and can be marketed .To increase the economic value of the family. The scavenger group at the Sukawinatan TPA location is expected to be fostered and can be used as an object of community service by a group of lecturers from Poltekkes Kemenkes Department of Midwifery in 2016. This scavenging group will be guided by 4 lecturers which will be carried out over a period of 2 semesters, namely the period March 2016 to August 2016 and September 2016 to December 2016. This activity is entitled Science and Technology for the Community (IbM) specification of protection against scavenger groups at the Sukawinatan Final Disposal Site (TPA) Palembang in 2016.